SEJARAH TARI TIMANG BANJAR DI KERATON KADRIYAH KOTA PONTIANAK KALIMANTAN BARAT - Murti, Elis Syahira; Ismunandar, Ismunandar; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is made because the writer interested in Malay dance that have dance title in a dance. The aim of this research is to find out the history of Timang Banjar in written documentation that supported by Timang Banjar photos related. Datas from this research is taken from some informants who knew about Timang Banjar dance dance, also include as the dancer used some research techniques. The research finding is the history of the Timang Banjar dance began in 1921, created by artist named Ncek Mat. This dance is worked as traditional dance on his leadership, first this dance is only showed in front of Vith Sultan from Kadriyah palace and only dance in Kingdom family big events. Then, to introduse this dance to people, especially people around Kadriyah palace, this dance is showed in art performance Tonel drama. Timang Banjar dance has to generations dancers after Ncek Mat. The development happened on dance presentation form. This dance started to appear again in 2016, in revitalization of Timang Banjar dance that taught by third generations to SMKN 7 Pontianak students.Keywords: history, development, Timang Banjar